(untitled) (Multidisciplinary Journal of Science and Technology, 2025)
The article examines the institutional, regulatory, and conceptual foundations for the introduction of independent student work within the higher education system of Uzbekistan. Particular emphasis is placed on its role in developing the professional competence of technical university students. It is shown that independent work is not a supplementary form of learning, but a key tool for fostering profession-oriented skills such as responsibility, critical thinking, self-organization, and the ability to apply knowledge in uncertain real-life conditions. The article concludes that the adoption of independent work practices is closely linked to the integration of national education into the Bologna Process and the ECTS system, which emphasize student-centered and outcome-based learning.